Dispositivos volitivos e não volitivos utilizados no treinamento e na terapia vocal - Batista, Denis de Jesus (2023)
Devices are one of the ingredients that optimize results in vocal interventions. Objective: Mapping, describing and categorizing the devices used by speech therapists in vocal interventions and in the scientific literature. Method: This dissertation is divided into two studies. 1) First, a cross-sectional study. 148 speech therapists with clinical practice in Voice answered a questionnaire about sociodemographic data, work and professional training. and about the use of devices in vocal interventions. Data collection was performed using Google Forms. Data were analyzed descriptively and inferentially. 2) According to a scoping review guided by the question: "What are the devices used in vocal interventions?". An electronic search was carried out in the databases: MEDLINE, LILACS, SCOPUS, Web of Science, EMBASE and Cochrane Library, and manual in the bases: BDTD, ASHA WIRE, Clinical Trials, Journal of Voice and ProQuest. Studies with adult or elderly participants who used a device in vocal intervention were included. Article selection and data extraction were performed by two blinded and independent reviewers. Disagreements were resolved by consensus. Data analysis was performed descriptively. Results: 1) Speech-language pathologists specializing in voice are more likely to use thermotherapy and not use elastic bandage, therapeutic ultrasound and nebulizer. Voice specialists are less likely to use electrostimulation. The time of voice performance determines the use of photobiomodulation and the device for feedback and auditory monitoring, length of speech therapy training influences the use of electrical stimulation; the age of the professional, in the use of vibratory stimulation. Voice professionals are more likely to use vibratory stimulation, auditory return and monitoring devices, thermotherapy and nebulization, and less chance for the nebulizer. In children, there is less chance for photobiomodulation; in adolescents, there are greater chances of using vibratory stimulation and, in the elderly, thermotherapy. 2) Publications using devices are current, mainly in the United States of America and Brazil, in behavioral dysphonia and in both genders. Forty-three types of devices were used, most voluntarily, with emphasis on the silicone tube targeting the vocal function, and mechanism of action in the source-filter interaction. Device dosage was controlled by time, and outcome measures, acoustic analysis and self-assessment. Conclusion: 1) Tubes, straws and masks were the most used devices. Title of specialist and specialization, time since training and performance, target population. are determinant in the use of devices. The focus of use of the devices was the vocal function The applicability of the devices was especially in behavioral dysphonia. The speech therapist qualifies for the use of the devices and prescribes it by time. In study 2, the use of devices gained notoriety in the last decade in the United States of America and Brazil. They are used in adults with behavioral dysphonia, of different genders. The silicone tube was the most used with a focus on vocal function, and with a mechanism of action, the source-filter interaction. The dosage is prescribed in time and the main evaluations are self-assessment and acoustic analysis.